Voices in the Hill: Stories of Trauma and Inspiration - Susan G. Goldberg; Camille O'Connor (The University of Alabama, 2022)
Narrative interviews documenting individual and community trauma in the Hill District of Pittsburgh emerged from a capstone undergraduate community engagement psychology course that was a joint project between Duquesne University and FOCUS Pittsburgh. The interview project, which we gave the name Voices in the Hill, sought life stories and existential meaning-making of people involved with the Hill District of Pittsburgh, a formerly flourishing African-American community now mired in poverty due to a juncture of sociological, historical, and political forces. Themes that emerged from the interviews included abuse, mental health issues, and failures of the larger society. With the facilitation of FOCUS Pittsburgh, we discuss how these traumatized people created existential meaning and empowerment in their lives. We explore how their individual stories emerged from larger societal processes such as racism, discrimination, and loss of community, as well as other impacts of "root shock." We also share the moving impact of the work on students.